THE EFFECTIVENESS OF CO-OP CO-OP & MAKE A MATCH COMBINATION MODELS IN ONLINE LEARNING - Lailatul Romandhon, Bintari Febriaty; Qudus, Nur; Sudana, I Made (Journal of Vocational and Career Education, 2020)
Combining Cooperation-Cooperative (Co-op Co-op) and Make a Match model can stimulate students to be active in online learning. Students were able to construct their knowledge independently by using the Co-op Co-op model. Learning atmosphere became attractive with finding the partner games during the class used the Make a Match model. This combination model made students more active and did not quickly feel bored. This research aimed to know the effectiveness of the Co-op Co-op and Make a Match model in online learning for based competency in operating survey tools and mapping to improve students’ achievement. The current research used quasi-experiment research. The experiment class consists of 35 ten grade students of Building Information Modeling (DPIB) one, while the control class consists of 36 ten grade students of Building Information Modeling (DPIB) two. Pre-test and post-test were given by using Google form to both groups. The average score of N-Gain achieved 75,9%, which means the implementation learning model was effective to advance students’ achievement. Independent sample T-test got T count = 4,59 > T. It can be said there was a significant difference in average score between experiment and control group. Furthermore, the students’ interest questionnaire achieved 84,5. In conclusion, Co-op Co-op and Make a Match model in online learning by using supporting tools (Google Meet, WhatApp group, etc.) not only effective to improve students’ achievement but also got positive responses from the participants. The teacher can use this combination model to improve students’ interest and achievement in online learning.